Research Infrastructures in the Humanities : The Past, The Present, and the Future - Žic Fuchs, Milena (Array, 2014)
This keynote lecture addresses the fundamental issue of the visibility of the RIs in the Humanities with the aim of addressing the global dimension of research as well as inter/multi/trans-disciplinarity. Apart from giving an overview of the past and present recommendations are made for establishing global RIs necessary for the ongoing resetting of research agendas, which by default imply bridging gaps between disciplines and crossing domain boundaries. Special attention is drawn to the necessity of setting up specific databases focused on research topics.